Hospital Time - Hoffman, Amy (Book collections on Project MUSE., 1997)
"Amy Hoffman, a writer, lesbian activist, and former editor of Gay Community News, chronicles with fury and unflinching honesty her experience serving as primary caretaker for her friend and colleague, Mike Riegle, who died from AIDS-related complications in 1992"--Cover